Influence of Irradiated Chitosan Coating on Postharvest Quality of Kinnow (Citrus reticulata Blanco.) - Abbas, Huma; Akhtar Abassi, Nadeem; Yasin, Tariq; Maqbool, Mehdi; Ahmad, Touqeer (Asian Journal of Chemistry, 2010)
The effect of coating with irradiated chitosan (CHIirr, Mv = 5.14 × 104) and unirradiated chitosan (CHIun, Mv = 2.61 × 105) on postharvest preservation of Kinnow (Citrus reticulata B) has been studied. 1 and 2 % coatings of both CHIirr and CHIun were used and the fruits were stored at 4 °C in 80 % relative humidity for 12 weeks. Changes in weight loss, ascorbic acid, titratable acidity, total soluble solids, reducing, nonreducing and total sugars were periodically measured during storage. Physical characteristics such as general appearance in colour and shape of the fruits and organoleptic evaluation were also carried out. All chitosan coating reduced the weight loss and respiration rate during storage. It also delayed and minimized the changes in: ascorbic acid contents, titratable acidity, etc. and maintained eating quality of fruits till 3 months as compared to untreated fruits.